How to relate to dialysis patients' fatigue - perspectives of dialysis nurses and renal health professionals: A qualitative study. (May 2021) - van der Borg, Wieke E.; Verdonk, Petra; de Jong-Camerik, Judith; Abma, Tineke A.
Abstract: Background: Although fatigue among the dialysis population is known as a severe and debilitating health problem, this symptom is often under recognized and undertreated. Objective: This qualitative study aimed to gain a better understanding of how dialysis nurses and renal health professionals perceive and address dialysis patient's fatigue in renal care practice. Design: We conducted a qualitative descriptive study to explore how nurses and renal health professionals perceive and address dialysis patients' fatigue in their daily health care practices. A constructivist grounded theory approach guided analysis and conceptualisation of findings. Setting(s): This study took place at 13 academic and regional settings across the Netherlands. The study was approved by the Medical Ethics Committee (2015.049), on behalf of VU University medical center in Amsterdam. Participants: Twenty-one renal health professionals of various disciplines took part in interviews: ten dialysis nurses, four nephrologists, two physician assistants, five medical social workers. Methods: Semi-structured interviews were conducted in order to gain in-depth insight into the perspectives of dialysis nurses and renal health professionals. An inductive thematic analysis provided insight into health professionals' stances toward dialysis patients' fatigue in light of their daily care context and practices. Results: Two main themes emerged; 1) 'Fatigue in the background': Shows there is strong focus on medical-technical aspects of the disease. All health professionals perceive fatigue as an intangible symptom that is difficult to address, and falls outside their scope of responsibility and competence. Communication about fatigue among professionals and with patients is limited, pushing fatigue further into the background. 2) 'Vulnerabilities in the background': Especially nurses and social workers signal the accumulating vulnerabilities of dialysis patients and associate these with fatigue (old age, multimorbidities, financial and social problems). Although the need for psychological support is acknowledged, multiple vulnerabilities increase the complexity and intensity of care, and further strengthens the medical-technical focus of care and treatment. Conclusions: There is a need to enable renal health professionals to communicate about the complex nature of fatigue in renal patients and stimulate interdisciplinary exchange and shared responsibility. Dialysis nurses have frequent contact with patients during dialysis treatment and are the first to notice when patients' fatigue increases and their overall condition deteriorates. They can play an important role to go beyond the technological imperative of care and understand the lived experiences of patients within their social contexts.